Pendampingan Usaha Mikro dan Masyarakat Desa Balunijuk dalam Mewujudkan Kampung HalalL - Occa Roanisca; Maya Yusnita; Robby Gus Mahardika (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
Halal product assurance is a global concern, especially in some Southeast Asian countries. The Government of Indonesia through law No. 33 of 2014 requires food and beverage products circulating in Indonesia to have halal certificates. Responding to the central government program, the Government of Bangka Belitung has issued a Regional Regulation on the Implementation of Safe and Halal Food Guarantees. The purpose of the Community Partnership Program (CPP) is to realize Balunijuk Village as Halal Village. The determination of these objectives is the result of an agreement between the village officials and food and beverage business people in Balunijuk Village. The method of implementation in this activity is in the form of direct guidance to six fostered partners to obtain a Sanitation Hygiene (HS) certificate, and socialization on halal lifestyle targeting the community, village officials and six fostered businesses. Six fostered businesses in the village of Balunijuk have received Sanitation Hygiene (HS) Eligible Certificates. The issuance of HS certificates in the foster stalls shows the seriousness of partners in maintaining the cleanliness of the production process, raw materials and sanitation of production sites. HS Certificate as a requirement for business actors to apply for a Halal Certificate LPPOM MUI in Bangka Belitung. As many as 90% of participants understood about halal lifestyle material, besides that participants felt the need to apply halal lifestyle, especially in the selection of food and drinks to be consumed because it had an impact on physical and spiritual health. The results of this activity are the initiators to realize Balunijuk Village as Halal Village.